Visualization of lipids in skeletal muscles by mass spectrometry imaging - Naoko Goto-Inoue; Tomohiko Sato; Nobuharu L. Fujii (Japanese Society of Physical Fitness and Sports Medicine, 2017)
Lipids are the major components of cells and, in addition to being involved in cell signaling, play a major role in the skeletal muscles. Lipids comprise a large number of molecular species with their different fatty acid compositions, and it is hard to visualize their spatial localization to identify muscle-fiber-specific lipid dynamics. In this short review, we present a molecular imaging technology, matrix-assisted laser desorption/ionization mass spectrometry imaging, capable of imaging small metabolites including lipids. This technology has the potential to reveal the lipid dynamics that occur during muscle contraction and/or disease status.